Extension of Dairy Products for School Age Students in Nagari Saniangbaka, X Koto Singkarak, Regency of Solok, West Sumatra - Aronal Arief Putra; Putri Amalia Sari; Sofia Ananda; Bagastra Khoosy Anakariksi; Khairunnisa Khairunnisa (Warta Pengabdian Andalas, 2024)
The extension of dairy products as a community service in Nagari Saniangbaka, X Koto Singkarak, Solok Regency was carried out. This project aimed to increase the knowledge and concern of school-age students about consuming dairy products. This project used UHT milk, fermented milk, and cheese to target students from SD 19 Saniangbaka, MDA Surau Gadang, and SD 34 Saniangbaka, respectively. The extension was divided into short lectures, discussions, quizzes, and product distributions. The activities of the three group participants increased the students' knowledge and interest in dairy products. The positive response from the participants was noticed, with MDA Surau Gadang students showing the highest enthusiasm for the activity conducted. This community service indirectly instills awareness of the importance of dairy food as a nutritious food source, especially for students in their growing years.